2016
DOI: 10.1001/jama.2016.12623
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Allergenic Food Introduction to the Infant Diet and Risk of Allergic or Autoimmune Disease

Abstract: Timing of introduction of allergenic foods to the infant diet may influence the risk of allergic or autoimmune disease, but the evidence for this has not been comprehensively synthesized. OBJECTIVE To systematically review and meta-analyze evidence that timing of allergenic food introduction during infancy influences risk of allergic or autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
343
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(385 citation statements)
references
References 39 publications
14
343
2
9
Order By: Relevance
“…These recommendations have been modified after studies failed to show a correlation between maternal diet and development of atopic disease [42] . In contrast to past recommendations, more recent studies have shown a protective effect of high allergen consumption during pregnancy [43] . High consumption of peanuts and tree nuts during pregnancy was found to be associated with lower rates of food allergy in children [44] .…”
Section: Allergic Sensitizationmentioning
confidence: 70%
“…These recommendations have been modified after studies failed to show a correlation between maternal diet and development of atopic disease [42] . In contrast to past recommendations, more recent studies have shown a protective effect of high allergen consumption during pregnancy [43] . High consumption of peanuts and tree nuts during pregnancy was found to be associated with lower rates of food allergy in children [44] .…”
Section: Allergic Sensitizationmentioning
confidence: 70%
“…Koplin et al [7] found similar results; introducing egg into the diet between 10 and 12 months was associated with a lower risk of developing egg allergy (odds ratio, OR 1.6, 95% CI 1.0–2.6) than egg introduction after 12 months (OR 3.4, 95% CI 1.8–6.5). This finding was supported by randomized controlled trials (RCTs) of peanut exposure [9, 10] and a single meta-analysis [11]. By intention to treat analysis, Perkin et al [10] found no difference in the decrease in egg allergy in UK infants fed with egg from 3 months of age compared to only breast-fed infants (3.7 vs. 5.4%, respectively), representing a 31% lower relative risk (RR).…”
Section: Introductionmentioning
confidence: 81%
“…Согласно рандомизированным исследованиям и данным метаанализа (1915 участников), полу-чены доказательства умеренной силы, что раннее введение яиц на сроке 4-6 мес жизни ассоци-ировано с более низким риском развития аллергии на яйцо в будущем в группах без риска, высокого риска и очень высокого риска развития аллергии (RR 0,56 [95% CI 0,36-0,87], р=0,009) [25]. В двух исследованиях сообщалось, что у младенцев, впер-вые употребивших яйца в сырой пастеризованной форме, могут развиться тяжелые аллергические реакции из-за предшествующей сенсибилизации, но таких эффектов не наблюдалось в испытаниях с употреблением приготовленного или подвергше-гося тепловой обработке яйца.…”
Section: оригинальные статьи в помощь практическому врачуunclassified
“…По данным метанализа [25], раннее введение рыбы в рацион ассоциировано с уменьшением частоты развития аллергической гиперчувстви-тельности и аллергического ринита. Ассоциаций с другими аллергическими и аутоиммунными за-болеваниями не обнаружено.…”
Section: оригинальные статьи в помощь практическому врачуunclassified